2020
DOI: 10.1038/s41598-020-57938-3
|View full text |Cite
|
Sign up to set email alerts
|

VCP expression decrease as a biomarker of preclinical and early clinical stages of Parkinson’s disease

Abstract: Valosin-containing human protein (VCP) or p97 performs enzyme functions associated with the maintenance of protein homeostasis and control of protein quality. Disruption of its normal functioning might be associated with the development of Parkinson's disease (PD). Tissues of mice with toxininduced presymptomatic and early symptomatic stages of PD, as well as 52 treated and untreated patients with newly diagnosed PD and nine patients with a "predicted" form of PD, were investigated. Significant changes in Vcp … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…Consistent with the findings of the present study, TER ATPase has also been reported in EVs released from various cancer cells [ 47 ] and its downregulation greatly reduces exosome secretion, suggesting targeting of TER ATPase as a new anti-tumor therapy approach [ 48 ]. Moreover, TER ATPase can serve as a biomarker for the development of pathology at the early clinical and preclinical stages of Parkinson’s disease in humans [ 49 ]. However, the role and diagnostic values of the EV TPx-1 and TER ATPase of E .…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the findings of the present study, TER ATPase has also been reported in EVs released from various cancer cells [ 47 ] and its downregulation greatly reduces exosome secretion, suggesting targeting of TER ATPase as a new anti-tumor therapy approach [ 48 ]. Moreover, TER ATPase can serve as a biomarker for the development of pathology at the early clinical and preclinical stages of Parkinson’s disease in humans [ 49 ]. However, the role and diagnostic values of the EV TPx-1 and TER ATPase of E .…”
Section: Discussionmentioning
confidence: 99%
“…Based on the literature review, we discover that some of these genes have been reported to be associated with PD. PACRG, TH, LRRK2, TNR, and VCP are reported in [35][36][37][38][39][40][41] . In addition, KCNJ2, APBB1, and DCTN1 genes are associated with neurodegenerative diseases [42][43][44] .…”
Section: /23mentioning
confidence: 92%
“…We used seven metrics for measuring the performance of our proposed system, which are accuracy (ACC), area under the curve (AUC), area under precision-recall curve (AUPR), F1-Score, Matthews correlation coefficient (MCC), sensitivity (SEN), and specificity (SPC) 33,34 , which are defined by equations (33)• • • (40).…”
Section: Evaluation Metricsmentioning
confidence: 99%
“…To test this methodology, we used neurotoxic animal models of clinical and preclinical stages of PD, which are characterized by threshold and subthreshold degradation of the nigrostriatal dopaminergic system, respectively. [51][52][53][117][118][119][120][121] In this case, PD was reproduced in mice C57BL by systemic administration of 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP), converted in the body to 1-methyl-4-phenylpyridinium, a toxin of dopaminergic neurons (Figure 1C,D). 116,122 Testing of this methodology showed that among 13 biomarkers found in untreated PD patients at the clinical stage, such as changes in plasma concentrations of catecholamines and amino acid neurotransmitters, as well as expression of specific genes in lymphocytes, 7 and 3 biomarkers were characteristics of models of PD at the clinical and preclinical stage, respectively.…”
Section: Searching For Biomarkers In Body Fluids In Patients and Animal Modelsmentioning
confidence: 99%